2010
DOI: 10.1590/s0365-05962010000600014
|View full text |Cite
|
Sign up to set email alerts
|

Does incomplete excision of basal cell carcinoma of the eyelid mean tumor recurrence?

Abstract: Introduction: Basal cell carcinoma is the most common tumor of the eyelid. In this region, reconstruction is complex and damage to healthy tissue should be minimal. Objective: To define the relationship between margin clearance at excision and the recurrence rate of basal cell carcinoma of the eyelid. Methods: This prospective study was conducted with 111 patients submitted to surgery for basal cell carcinoma of the eyelid between 2001 and 2003 and followed up for a period of five years. The patients were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 30 publications
2
14
0
3
Order By: Relevance
“…The presence of medial canthal tendon, the upper lacrimal drainage system and the orbital septum attachments may lead the surgeon to be more cautious in an attempt to preserve these structures during tumour excision. Jankovic et al 23 reported that there is no statistically significant association between incomplete BCC excision and tumour recurrence except for medial canthus BCC.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of medial canthal tendon, the upper lacrimal drainage system and the orbital septum attachments may lead the surgeon to be more cautious in an attempt to preserve these structures during tumour excision. Jankovic et al 23 reported that there is no statistically significant association between incomplete BCC excision and tumour recurrence except for medial canthus BCC.…”
Section: Discussionmentioning
confidence: 99%
“…8 In addition, radiotherapy does have potential side effects: alopecia, cataract, conjunctivitis, corneal exposure, dermatitis, dry eye, lachrymal duct stenosis, ocular ischemia, optic neuropathy, pain, red eye, and retinopathy. 9 A drawback to radiation therapy is that it can usually only be given once to each location.…”
Section: Resposta / Replymentioning
confidence: 99%
“…Assim, quanto menor o defeito, melhor o resultado. (28,29,38) Dentre as variáveis que pudessem alterar a acurácia, investigamos o tamanho tumoral (diâmetro e área) pela possibilidade de tumores maiores poderem expressar maior multiplicidade de padrões histológicos, embora um estudo tenha sugerido que o tamanho do tumor não influenciaria a representatividade na biópsia. (84) No presente estudo, também verificamos que a acurácia da biópsia por trépano independe do tamanho do tumor.…”
Section: Discussionunclassified
“…(35,37) Recomenda-se cirurgia imediata de lesões excisadas incompletamente, principalmente quando o defeito remanescente foi tratado com retalho ou enxerto de pele, e também para lesões do canto medial com margens pequenas. (30,37,38) Entretanto, ressecção incompleta não significa, necessariamente, recorrência do tumor. Provavelmente por ação do sistema imune, da inflamação local, do processo de cicatrização ou da desvitalização tecidual, o tumor residual é removido e o CBC não recidiva em mais de 50% dos casos com margens positivas.…”
Section: Tipos De Pele Descriçõesunclassified
See 1 more Smart Citation